Quinolones affect thymidine incorporation into the DNA of human lymphocytes. - Forsgren, A (1986)
The incorporation of [3H]thymidine into DNA was increased in phytohemagglutinin-stimulated human lymphocytes exposed to four of the new quinolone derivatives (ciprofloxacin, norfloxacin, ofloxacin, and A 56620) at concentrations achievable in clinical situations. However, proliferation of phytohemagglutinin-stimulated lymphocytes was not influenced by ciprofloxacin at concentrations of 0.5 to 10 micrograms/ml.